Strategi Promosi Produk Kopi dalam Menaikkan Angka Penjualan Produk di Pondok Pesantren Mukmin Mandiri Sidoarjo - Hidayati, Nurul (Jurnal Administrasi Pendidikan Islam, 2024)
This study aims to determine the promotional strategy carried out by Pondok Pesantren Mukmin Mandiri Sidoarjo to increase sales of its product, namely coffee. Sales is a way to stimulate purchases immediately or to increase the number of purchases made by customers. Of course, if you want to market an item so that many customers do promotions. Without product promotion, it is likely that the product will not attract customer attention. This study used a qualitative method, namely by using literature and interview techniques. Interviews are needed because this research requires the opinion of the school principal and school members and also this research refers to field studies so interviews are needed. Meanwhile, literature study is needed because it is necessary to see several references that are relevant and in accordance with what will be studied. The result of this research is the need for promotional activities to promote coffee products so that people are interested and know about the existence of these coffee products.